Sixty‐five years of change, from annuals to subshrubs: Diachronic vegetation dynamics in the halophytic–steppe ecotone of Chott Chergui, a Mediterranean semi-arid depression, Algeria - Benkhettou, Mohamed; Benkhettou, Ghania; Benkhettou, Abdelkader; Taibi, Khaled (Mediterranean Botany, 2026)
The current study presents a comprehensive 65-year diachronic analysis of the Atriplex mauritanica-Suaeda fruticosa subassociation in eastern Chott Chergui, Algeria. By resurveying historical plots from 1954 in 2019, the present study quantifies shifts in taxonomic composition, life‐form spectra, biogeographic affinities, and diversity metrics (Shannon-Wiener index, Pielou’s evenness, Margalef’s richness, Jaccard similarity, Cohen’s d). Species richness declined by 26.1 %, with therophytes decreasing from 68 % to 51 % and chamaephytes increasing from 19 % to 31 %. A significant decline in Shannon diversity (from 3.97 to 3.70, Welch’s t = 3.12, p<0.001) and a Jaccard similarity of only 0.46 confirm substantial floristic turnover. Endemic taxa persisted (100 %), while mesic Mediterranean and pluri-regional elements contracted. The emergence of Saharo‐Sahelian Atractylis serratuloides highlights ongoing xerophytization under accelerating aridification. Conservation of this fragile ecosystem demands a combination of livestock exclusion and soil restoration, along with continuous climate monitoring. These efforts should be underpinned by multivariate and trait‐based analyses to pinpoint the drivers of change. Beyond documenting a hallmark of Mediterranean desertification, our study delivers a concise, transferable framework for long‐term vegetation‐change assessments in other climate‐sensitive steppes.